A comparative study of root canal shaping using protaper universal and protaper next rotary files in preclinical dental education - Gül Çelik; Feyza Özdemir Kısacık; Emir Faruk Yılmaz; Arife Mersinlioğlu; İhsan Furkan Ertuğrul; Hikmet Orhan (PeerJ, 2019)
Background Dentistry has undergone an evolution in endodontics practice caused by the advancement of rotary techniques for root canal preparation and their subsequent incorporation into the teaching of dentistry undergraduates. This research aimed to evaluate the shaping ability of third-year dental students as their first experience in rotary instrumentation using ProTaper Universal (PTU) and ProTaper Next (PTN) (Dentsply Maillefer) rotary instruments in simulated curved canals. Methods Forty students instrumented 200 simulated canals with a 40° curvature in resin blocks according to the manufacturer’s instructions with PTU and 39 students and 195 canals with PTN files. The canals were prepared at a speed of 300 rpm using a 16:1 reduction hand-piece powered by an electric motor (Xsmart; Dentsply Maillefer). The final apical preparation was set to F2 for the PTU and X2 for the PTN group. The change in canal curvature was evaluated based on Schneider technique using the AutoCAD 2007 software on post-digital photographs. The incidence of instrument fracture and deformation, the incidence of ledge, the change in working length (WL), and the working time were noted. The data were analyzed with Student’s t-test and Chi-Square test at a significance level of 0.05 using SPSS. Results PTN maintained the original canal curvature better, resulting in fewer fractures and ledges, and shaped the canals faster than the PTU (P < 0.05). The mean curves of the resin canals after the instrumentation for the PTU and PTN groups were 24.03° ± 3.14° and 25.64° ± 2.72°, respectively. Thirty-three (17.4%) PTU and 18 (9.3%) PTN files fractured (p < 0.05). Nine (4.5%) PTU and 2 (2.6%) PTN deformed (p > 0.05). The change in WL after instrumentation was 0.97 mm ± 0.95 mm in PTU and 0.96 mm ± 0.80 mm in PTN (p < 0.05). The mean times were 627 s ± 18 s for PTU and 379 s ± 18 s for PTN (p < 0.000). Discussion PTN can be recommended in severely curved root canals in terms of maintenance of the original canal curvature, superior instrument fracture and fewer ledges. Even if training before preparation provides an acceptable level of canal shaping for preclinical students, the use of NiTi rotary instruments should be included in the undergraduate dental curriculum, contributing to an increase in the quality of root canal shaping and, consequently, to an improvement of the clinical experience of students.